Conversion Design of Arduino-Based Semi-Automatic Clothes Washer - Hariono, Tholib; Indryanto, Surya Puji; Munawarah, Munawarah; Ashoumi, Hilyah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research aims to develop and evaluate a system that converts a manual clothes washer into an Arduino-based semi-automatic one. The research method used is a method of designing and creating a system for the object of research or called the design method. The system design is used as an object where the system is discussed and tested to find out how the system works and performs itself. The design object is an efficient and practical clothes washing tool.Converting a manual clothes washer into an Arduino-based semi-automatic one is an innovative and efficient solution to increase convenience and effectiveness in the clothes washing process. The design of this conversion model provides a complete guide to convert a manual washing machine into a semi-automatic one, improving the efficiency and convenience of daily use. With proper implementation, this project can provide an effective and cost-effective solution for household users.